Reflections on the Asian American and Pacific Islander Experience: Not a Monolith—a Movement. Issue 2 (August 2021) - Wang, Victoria; Wang, Michelle J.; Lee, Yeon Woo
Abstract : We deconstruct the historical frameworks that perpetuate Asian American and Pacific Islander (AAPI) invisibility, share examples of their effects on clinical work, and provide resources for improving AAPI allyship.